2015
DOI: 10.1007/s11999-014-3648-0
|View full text |Cite
|
Sign up to set email alerts
|

Does Increased Topside Conformity in Modular Total Knee Arthroplasty Lead to Increased Backside Wear?

Abstract: Background Modular metal-backed tibia components allow surgeons intraoperative flexibility. Although it is known that modular tibia components introduce the possibility for backside wear resulting from relative motion between the polyethylene insert and the tibial baseplate, it is not known to what degree variability in the conformity of the tibial polyethylene liner itself might contribute to backside wear. Questions/purposes The purpose of this study was to determine whether a flat, cruciate-retaining tibial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…This correlation is corroborated in multiple other retrieval studies [1,3,4,18]. There also are varying degrees of evidence that backside wear is increased by other implant factors such as polyethylene sterilization in noninert gas [2,5,6,9,25,40], polyethylene manufacturing [16,27], tibial baseplate composition [3,4,7], conformity of the polyethylene articular surface [36], and polyethylene thickness [13,44]. In some studies, patient factors such as longer time in vivo of the polyethylene [17,21,31], increased patient weight [8], male sex, and younger patient age [16] have been shown to increase backside wear.…”
Section: Introductionsupporting
confidence: 54%
“…This correlation is corroborated in multiple other retrieval studies [1,3,4,18]. There also are varying degrees of evidence that backside wear is increased by other implant factors such as polyethylene sterilization in noninert gas [2,5,6,9,25,40], polyethylene manufacturing [16,27], tibial baseplate composition [3,4,7], conformity of the polyethylene articular surface [36], and polyethylene thickness [13,44]. In some studies, patient factors such as longer time in vivo of the polyethylene [17,21,31], increased patient weight [8], male sex, and younger patient age [16] have been shown to increase backside wear.…”
Section: Introductionsupporting
confidence: 54%
“…This study was subject to several limitations. First, we used a pin‐on‐disk test method, so the shapes of the pin‐and‐disk specimens were different from those of the joint replacements, whereas Schwarzkopf et al reported that the conformity of the bearing surface affected the backside damage of PE . However, the roughness of the bearing surface of the pin‐and‐disk specimens was similar to that of the artificial joint products.…”
Section: Discussionmentioning
confidence: 86%
“…The polyethylene is often secured to the tray by one of a variety of proprietary locking mechanisms, comprising a fixed‐bearing device. A frequently cited reason for failure of these knee replacements is wear of articular and/or backside (non‐articular) surface of this polyethylene tibial insert …”
mentioning
confidence: 99%
“…For knee replacement patients, the sub‐micron polyethylene debris produced by wear of the tibial insert can cause a number of negative outcomes including synovitis, aseptic loosening, and osteolysis . Although in fixed‐bearing tibial constructs the polyethylene is captured by the metal tray, previous studies have indicated that the backside surface of the tibial insert can move relative to the tray, and this micro‐motion is a potential source of significant debris .…”
mentioning
confidence: 99%